2022
DOI: 10.1021/acs.energyfuels.2c00689
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Efficiency of Coal Bed Methane Recovery by Injecting Carbon Dioxide Based on an Anthracite Coal Macromolecular Model and Simulation Methods

Abstract: Enhancing the efficiency of coal bed methane (CBM) recovery by injecting carbon dioxide (CO2) is regarded as an effective method to exploit CBM, and CO2 geological sequestration also mitigates greenhouse gas emissions. In this study, 13C nuclear magnetic resonance (13C NMR) spectroscopy, Fourier transform infrared (FTIR) spectroscopy, and X-ray photoelectron spectroscopy (XPS) experiments are employed to construct a two-dimensional (2D) chemical molecular structure. The 2D chemical molecular structure is annea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 79 publications
0
3
0
Order By: Relevance
“…The desorption curve experiences a decline indicating that only a limited number of methane molecules can desorb, with the residual gas being retained [30]. This condition worsens when small pores reach maximum adsorption capacity, leading to dominant swelling effects in the coal matrix [31]. Due to various factors, the CH 4 trapped in coal seams cannot be released smoothly, which may hinder CH 4 recovery improvement.…”
Section: The Effective Methods For Ecbmmentioning
confidence: 99%
“…The desorption curve experiences a decline indicating that only a limited number of methane molecules can desorb, with the residual gas being retained [30]. This condition worsens when small pores reach maximum adsorption capacity, leading to dominant swelling effects in the coal matrix [31]. Due to various factors, the CH 4 trapped in coal seams cannot be released smoothly, which may hinder CH 4 recovery improvement.…”
Section: The Effective Methods For Ecbmmentioning
confidence: 99%
“…Micropores and mesoporous pores in coal are the main adsorption sites for methane. In this paper, we used the 3D macromolecular structure as a basis, a 1 nm blank slit layer was constructed and the adsorption behavior of methane was studied using the large canonical ensemble Monte Carlo (GCMC) simulation method using the adsorption module in Materials Studio software (version 19.1.0.2353) [46,60].…”
Section: Adsorption Simulation Methodsmentioning
confidence: 99%
“…With the development of computer technology and simulation software, simulation technology has been shown to greatly reduce the cost of material development and improve work efficiency [ 21 , 22 , 23 , 24 , 25 , 26 ]. A molecular dynamic simulation optimization experiment showed that an efficiency ratio of running time that tended to balance judgment achieved the highest value of 36.96% [ 27 ].…”
Section: Introductionmentioning
confidence: 99%